IIT BHU at fire 2018 Irmidis track - Obtaining factual tweets during natural disasters - Mehrotra H.; Pal S. (My University, 2025)
This paper presents details of the work done by the team of IIT (BHU) Varanasi for the IRMiDis track in FIRE 2018. The task involved classifying tweets posted during a disaster into those which are fact-checkable or factual and which are not, and also match these tweets to relevant news articles. Methodologies had to be developed in context of the 2015 Nepal Earthquake. © 2018 CEUR-WS. All Rights Reserved.